The Role of the Educational Supervisor in Developing Scientific Research Skills and the Challenges Facing Family and Health Education Teachers at the Secondary Stage in Jeddah - Al-hazmi, Nujood Abdulazize (Journal of Educational and Psychological Sciences, 2021)
This study aimed to uncover the role of the educational supervisor in developing scientific research skills and the challenges facing family and health education teachers at the secondary stage in Jeddah, and to know the extent of the presence of statistically significant differences for the variable (educational qualification, specialization, and years of experience). This study followed the descriptive analytical method, and the questionnaire as a tool. The sample of the study consisted of family education teachers for Jeddah secondary school, as the sample size reached (171) female teachers, which showed the following results: The supervisors sometimes contribute to developing their skills in scientific research. There are challenges facing female supervisors in developing scientific research skills. There were no significant differences in the teachers ’opinions on the role of the supervisor, according to their qualifications. Also there was no moral difference between the teachers ’opinions on the educational supervisor’s role in developing scientific research skills according to years of experience. Important recommendations of the study: The necessity of strengthening the relations between supervisors and teachers because of its impact on the acceptance of the teacher’s attendance of training courses and thus their development on the personal and professional level, it's importance to provide teachers with teaching methods that contribute to forming positive directions that raise the spirit of belonging to the educational institution on teachers and motivate them to working and increasing their efficiency, the need to increase awareness of female teachers of the relationship between procedural research and growth.
Keywords: The Supervisor Educational; Skills Development; Education Family; Challenges